Longitudinal photocurrent spectroscopy of a single GaAs/AlGaAs v-groove quantum wire. - Cade, N; Hadjipanayi, M; Roshan, R; Maciel, A; Ryan, J; Macherey, F; Schäpers, T; Lüth, H (2005)
Modulation-doped GaAs v-groove quantum wires (QWRs) have been fabricated with novel electrical contacts made to two-dimensional electron-gas (2DEG) reservoirs. Here, we present longitudinal photocurrent (photoconductivity/PC) spectroscopy measurements of a single QWR. We clearly observe conductance in the ground-state one-dimensional subbands; in addition, a highly temperature-dependent response is seen from other structures within the v-groove. The latter phenomenon is attributed to the effects of structural topography and localization on carrier relaxation. The results of power-dependent PC measurements suggest that the QWR behaves as a series of weakly interacting localized states, at low temperatures.